Implementation Of Joint Venture Agreement From Law Number 25 Of 2007 Concerning Investment - Moh. Asep Suharna (Jurnal Mantik, 2022)
As a logical consequence of a joint venture, various problems arise, namely contractual problems between foreign parties and national parties in making joint venture agreements and dispute resolution issues between investors and the host country, there are doubts among foreign investors. In other words, the objectivity of the dispute resolution agency is doubtful. In Indonesia, there is a tendency for investors to choose to settle investment disputes out of court. The purpose of this study is to analyze the implementation of the joint venture agreement in terms of Law Number 25 of 2007 concerning Investment ? and problems that arise in the implementation of the joint venture agreement and how to resolve the dispute. The research method used in this research is descriptive analytical, with a normative juridical approach. This research was conducted by means of library research and field research with data collection techniques through documentation studies and interviews as well as data analysis methods used in this study using qualitative juridical analysis. Based on the results of research and discussion, the following conclusions can be drawn: First, the implementation of the joint venture agreement requires very serious handling and requires professionalism from both parties in order to avoid things that arise from the implementation of the joint venture agreement; Second, the problems that arise in the implementation of the joint venture agreement are due to the distribution of shares of 49% (national) and 51% (foreign) so that foreign companies can make important decisions because the shares are more than half, the distribution of shares is usually small, each only have only 20%, there is a transfer of shares to another party, because of dissatisfaction. The existence of these problems gives rise to investment disputes and efforts that can be made in accordance with the Capital Market Law in the form of dispute resolution by way of deliberation and consensus, arbitration or courts, and specifically for disputes between the government and foreign investors, disputes are resolved through agreed international arbitration.